Effects of Orthographic Forms on Second Language Speech Production and Phonological Awareness, With Consideration of Speaker‐Level Predictors. Issue 4 (17th July 2020) - Bassetti, Bene; Mairano, Paolo; Masterson, Jackie; Cerni, Tania
Abstract: Orthographic forms (spellings) can affect pronunciation in a second language (L2); however, it is not known whether the same orthographic form can affect both L2 pronunciation and metalinguistic awareness. To test this, we asked 260 speakers of English—first‐language (L1) English speakers, L1 Italian and L2 English sequential bilinguals, and L1 Italian learners of L2 English—to perform word repetition tasks and rhyme judgment tasks for word pairs containing the same consonant or vowel spelled with a letter or a digraph. L1 Italian speakers established a long–short contrast and used consonant and vowel length contrastively in their L2 English, both in production and in an awareness task. This provides evidence for a direct link between the effects of the same orthographic phenomenon on speech production and on metalinguistic awareness. Results were strengthened by combining experimental and qualitative data in the study of orthographic effects. Finally, the results show that proficiency predicts orthographic effects, and that orthographic effect predictors vary in naturalistic and instructed contexts. Abstract :